How technology is empowering patients? A literature review. (28th May 2013) - Calvillo, Jorge; Román, Isabel; Roa, Laura M.
Abstract: Background: The term 'Patient Empowerment' (PE) is a growing concept – so in popularity as in application – covering situations where citizens are encouraged to take an active role in the management of their own health. This concept is serving as engine power for increasing the quality of health systems, but a question is still unanswered, 'how PE will be effectively achieved?' Beyond psychological implications, empowerment of patients in daily practice relies on technology and the way it is used. Unfortunately, the heterogeneity of approaches and technologies makes difficult to have a global vision of how PE is being performed. Objective: To clarify how technology is being applied for enhancing patient empowerment as well as to identify current (and future) trends and milestones in this issue. Search strategy: Searches for relevant English language articles using Medline, Scopus, ACM Digital Library, Springer Link, EBSCO host and ScienceDirect databases from the year 2000 until October 2012 were conducted. Among others, a selection criterion was to review articles including terms 'patient' and 'empowerment' in title, abstract or as keywords. Main results and conclusions: Results state that practical approaches to empower patients vary in scope, aim and technology. Health literacy of patients, remote access to health services, and self‐care mechanisms are the most valued ways to accomplish PE. Current technology already allows establishing the first steps in the road ahead, but a change of attitude by all stakeholders (i.e. professionals, patients, policy makers, etc.) is required.